2019
DOI: 10.3171/2017.8.jns17459
|View full text |Cite
|
Sign up to set email alerts
|

Fifty shades of gradients: does the pressure gradient in venous sinus stenting for idiopathic intracranial hypertension matter? A systematic review

Abstract: OBJECTIVE The role of venous sinus stenting (VSS) for idiopathic intracranial hypertension (IIH) is not well understood. The aim of this systematic review is to attempt to identify subsets of patients with IIH who will benefit from VSS based on the pressure gradients of their venous sinus stenosis. METHODS MEDLINE/PubMed was searched for studies reporting venous pressure gradients across the stenotic segment of the venous sinus, pre- and post-stent pressure gradients, and clinical outcomes after VSS. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…McDougall and colleagues set out to answer this question by reviewing a total of 186 patients from 32 studies who underwent stenting and comparing their prestent TSG with clinical and visual outcomes. 66 They found that those with "favorable" outcomes had a higher mean prestent TSG of 22.8 mm Hg (vs. 17.4 mm Hg in those with unfavorable results) and a higher change in the TSG of 19.4 mm Hg (vs. 12.0 mm Hg). In a multivariate analysis controlling for other factors, the change in TSG correlated with the outcome; 94.2% of those with a TSG greater than 21 had a favorable outcome compared with only 82% of patients with a TSG 21 mm Hg.…”
Section: Transstenotic Gradientmentioning
confidence: 96%
“…McDougall and colleagues set out to answer this question by reviewing a total of 186 patients from 32 studies who underwent stenting and comparing their prestent TSG with clinical and visual outcomes. 66 They found that those with "favorable" outcomes had a higher mean prestent TSG of 22.8 mm Hg (vs. 17.4 mm Hg in those with unfavorable results) and a higher change in the TSG of 19.4 mm Hg (vs. 12.0 mm Hg). In a multivariate analysis controlling for other factors, the change in TSG correlated with the outcome; 94.2% of those with a TSG greater than 21 had a favorable outcome compared with only 82% of patients with a TSG 21 mm Hg.…”
Section: Transstenotic Gradientmentioning
confidence: 96%
“…1 Venous sinus stenting (VSS) has emerged as a safe and effective treatment option for patients with refractory IIH with associated venous sinus stenosis. 2 3 Metaanalyses have suggested roughly 90% improvement in papilledema, 80% improvement in visual symptoms, and 80% improvement in headache, [4][5][6][7][8][9] with major complication rates ranging from 1-7%. [5][6][7][8][9][10] The literature offers limited guidelines or recommendations for patient selection or treatment for IIH.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there is no significant difference in the pre-operative pressure gradient between stenting and medical treatment groups in intrinsic type of stenosis. Previous studies have reported that those with favorable outcomes had a higher mean pre-stent trans-stenotic pressure gradient [ 7 , 32 ]. Our results confirmed this finding.…”
Section: Discussionmentioning
confidence: 99%